SRI-Linked Sukuk: An Enabler for the Transition to Low-Carbon Activities - Normarianie Razali; Rusni Hassan; Nor Razinah Mohd Zain; Mohd Rizal Suratman (Journal of Islamic Finance, 2023)
In achieving a low-carbon economy, the Securities Commission Malaysia (SC) is facilitating companies, particularly the high-emitting greenhouse gas industry moving towards low-carbon activities with the issuance of the SRI-linked Sukuk Framework (SRILSF). This paper will analyse the SRILSF, explore the features of the SRI-linked sukuk and innovation by the issuer in selecting the Key Performance Indicators (KPIs) and Sustainable Performance Targets (SPTs) and finally, an observation of the issuance toward the institutional investors with sustainable portfolio. This paper adopted content analysis to study the characteristics, and core components of the SRILSF. Additionally, a comparative study was performed to exhibit different requirements between SRILSF with SRI Sukuk Framework and International Capital Market Association (ICMA)’s Sustainability-Linked Bond Principles (SLBP). Finally, this paper will provide an analytical review of available sustainability-linked sukuk issued in Malaysia, focusing on the core component of the sukuk. The paper acknowledges that ICMA’s SLBP is a voluntary adoption of the issuing process, while SRILSF is a Framework issued by a capital market regulator where one need complies to make an issuance, and non-compliance will result in a breach of such Framework. This paper also acknowledges there are different requirements set for the appointment of an external reviewer for post-issuance, and the credential requirements of the external reviewers set ICMA’s SLBP and SRILSF. The issuance of SC’s SRILSF is an important milestone in sustainable regulatory development of Malaysian capital market as it provides opportunities for Malaysian’ capital market issuers that seek to transition or commit to sustainable objective. The issuance of SRI-linked sukuk will attract more sustainable-focused investor, specifically institutional investors with sustainable portfolios.